Angular variation of pinning near the irreversibility temperature in single crystal Y Ba2Cu3O7−δ with splayed columnar defects - Nieva, Gladys; Herbsommer, J.A.; Luzuriaga, J.; Civale, L.; Nieva, G.; Pasquini, G.; Lanza, H.; Levy, P. (Elsevier, 1998)
Fil: Herbsommer, J.A. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina